Seismic attribute analysis of deep-water Dangerous Grounds in the South China Sea, NW Sabah Platform region, Malaysia - Banerjee, A. (Elsevier B.V., 2020)
The Sabah Basin is a prolific hydrocarbon province in Southeast Asia and has a significant economic impact on this part. Recent discoveries in the deep-water hydrocarbon prospects in the Northwest Sabah Trough prompted a comprehensive investigation of the surrounding area, e.g., Dangerous Grounds for hydrocarbon prospectivity. Previous studies in the Dangerous Grounds mainly focused on the sparse 2D seismic and gravity-magnetic data analysis. A systematic review of detailed depositional history has not been presented so far in the published literature. To achieve this, recently acquired high-resolution 3D seismic data and well information have been used for seismic attribute analysis to establish the structural features and depositional pattern from the Paleocene to recent age. Two major sedimentary sequences have been evaluated from the seismic data, which include syn-rift and post-rift sequence. The pre-rift sequence considered to be the acoustic basement is overlain by syn-rift sequence, deposited during the Paleocene to Early Oligocene age. Spectral decomposition analysis demarcates paleo-lows/depocenters, consist of siliciclastic sedimentary fills in grabens and half grabens with the syn-sedimentary deformation. Geobody interpretation helps to understand the different phases of syn-sedimentary faulting with the presence of antithetic faults in the grabens. Late Oligocene to Middle Miocene carbonate platform and reefs has been observed on top of the pre-existing structural highs. Sweetness attributes enable to appraise the reef structure to demarcate lithofacies boundaries. Variance and amplitude extraction maps reveal the development of reefs on top of the carbonate platform. Amplitude extraction map reflects the Late Oligocene to Middle Miocene channel-levee complex with the convex upward unconsolidated sand filling pattern. Sweetness map helps to delineate the meandering channel boundary, channel geomorphology with ox-bow lake, point bar, and west to east channel shifting. Carbonate and clastic dominated areas have been differentiated in the southwest part. Slides and debris flow Mass Transport Deposits, Late Miocene turbidites have been observed above the Middle Miocene Unconformity and evaluated based on their distinct seismic characteristics. During the Pliocene to recent, the basin has witnessed the deposition of thick pelagic-hemipelagic sediments in the outer-neritic to the bathyal environment in the passive margin condition. Â© 2020 Elsevier B.V.